Cytotoxic Effect of Gliotoxin from Candida spp. isolated from Clinical Sources Against Cancer and Normal Cell Lines. - Mahdi Al-Dahlaki, Noorulhuda O.; Shanter Al-Qaysi, Safaa Al-Deen A. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Invasive fungal infections have become more common during the past two decades. Candida species are the most common human fungal infections. These infections are characterized by internal injuries because of virulence factors, such as gliotoxin which is a fungal toxin that is thought to be antibacterial, antifungal, and antiviral.Objectives: To test the ability of Candida species obtained from clinical sources to produce gliotoxin as a virulence factor and investigate its cytotoxicity effects against some selected cell lines.  Materials and Methods: One hundred and ten clinical isolates of Candida species were obtained from patients attending hospitals in Baghdad from September 2021 to March 2022. They were diagnosed and characterized by routine laboratory methods and cultures. The capability of Candida isolates to secrete the gliotoxin was tested and measured by analytical methods. The cytotoxicity of produced gliotoxin was applied against normal and cancer cell lines.Results: The 110 yeast isolates were diagnosed and identified as follows: Candida albicans, Candida tropicalis, Candida parapsilosis, Candida glabrata, Candida Krusei, Candida kefyr, Candida lusitaniae, Candida rugosa. Twenty-eight Candida isolates showed gliotoxin production. The cytotoxicity effects of gliotoxin were reported against lymphocytes and AMGM and AMJ13 cell lines in different concentrations. The highest cytotoxic effect was noticed in the concentration of 400 µg/mL of gliotoxin.Conclusion: The results indicated that the pathogenicity of Candida was distributed among all ages, both sexes, and several types of sources of clinical isolates. Gliotoxin had an effect on normal and cancer cells.